Análisis espacial de las distancias a los principales centros urbanos de la Cuenca del Río Luján - Montes Galbán, Eloy (2017)
This paperwork aimed to analyze the spatial distribution of urban / rural areas and its distance from the mayor urban centers in districts of Lujan River basin. By using quantitative spatial analysis procedures such as cartography of statistic data, distance analysis, descriptive statistics by zone and profiling it was evaluated the relationship between urban/rural areas and major downtowns. Obtained results allow the advance made by quantitative Geography approach in methodological and conceptual aspects through corroborating or denying initial hypotheses and following approximation of new hypotheses about real situation of the studied area.